Bordetella pertussis Whole Cell Immunization, Unlike Acellular Immunization, Mimics Naïve Infection by Driving Hematopoietic Stem and Progenitor Cell Expansion in Mice - Varney, Melinda E.; Boehm, Dylan T.; DeRoos, Katherine; Nowak, Evan S.; Wong, Ting Y.; Sen-Kilic, Emel; Bradford, Shebly D.; Elkins, Cody; Epperly, Matthew S.; Witt, William T.; Barbier, Mariette; Damron, F. Heath (Frontiers in Immunology, 2018)
Hematopoietic stem and progenitor cell (HSPC) compartments are altered to direct immune responses to infection. Their roles during immunization are not well described. To elucidate mechanisms for waning immunity following immunization with acellular vaccines (ACVs) against Bordetella pertussis (Bp), we tested the hypothesis that immunization with Bp ACVs and whole cell vaccines (WCVs) differ in directing the HSPC characteristics and immune cell development patterns that ultimately contribute to the types and quantities of cells produced to fight infection. Our data demonstrate that compared to control and ACV-immunized CD-1 mice, immunization with an efficacious WCV drives expansion of hematopoietic multipotent progenitor cells (MPPs), increases circulating white blood cells (WBCs), and alters the size and composition of lymphoid organs. In addition to MPPs, common lymphoid progenitor (CLP) proportions increase in the bone marrow of WCV-immunized mice, while B220+ cell proportions decrease. Upon subsequent infection, increases in maturing B cell populations are striking in WCV-immunized mice. RNAseq analyses of HSPCs revealed that WCV and ACV-immunized mice vastly differ in developing VDJ gene segment diversity. Moreover, gene set enrichment analyses demonstrate WCV-immunized mice exhibit unique gene signatures that suggest roles for interferon (IFN) induced gene expression. Also observed in naïve infection, these IFN stimulated gene (ISG) signatures point toward roles in cell survival, cell cycle, autophagy, and antigen processing and presentation. Taken together, these findings underscore the impact of vaccine antigen and adjuvant content on skewing and/or priming HSPC populations for immune response.